2016
DOI: 10.1111/mve.12163
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of real‐time PCR assays for bloodmeal identification in Culicoides midges

Abstract: Culicoides (Diptera: Ceratopogonidae) midges are the biological vectors of a number of arboviruses of veterinary importance. However, knowledge relating to the basic biology of some species, including their host-feeding preferences, is limited. Identification of host-feeding preferences in haematophagous insects can help to elucidate the transmission dynamics of the arboviruses they may transmit. In this study, a series of semi-quantitative real-time polymerase chain reaction (qPCR) assays to identify the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Identification of arthropod blood meals by qPCR has been applied to sand flies, biting midges, kissing bugs, fleas and mosquitoes [22,23,[31][32][33][34][35]. Most of these were SYBR green-based systems; only three were probe-based.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of arthropod blood meals by qPCR has been applied to sand flies, biting midges, kissing bugs, fleas and mosquitoes [22,23,[31][32][33][34][35]. Most of these were SYBR green-based systems; only three were probe-based.…”
Section: Discussionmentioning
confidence: 99%
“…b Comparison for mixed blood meals (detected, n = 19; undetected, n = 22) not grouped according to host species. Asterisk (*) indicates significant difference (P < 0.05) between groups (Studentʼs t-test) and did not include humans, pigs or dogs [23], another was for identifying blood-meal hosts of biting midges and included humans and pigs but not dogs [33] and another was for identifying flea blood meals and included humans and dogs but not pigs [35]. Notably, the human probe in the latter flea blood-meal study was tested here and found to cross-react with dog DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of arthropod blood meals by qPCR has been applied to sand flies, biting midges, kissing bugs, fleas and mosquitoes [22,23,[31][32][33][34][35]. Most of these were SYBR green-based systems; only three were probe-based.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of arthropod bloodmeals by qPCR has been applied to sand flies, biting midges, kissing bugs, fleas and mosquitoes [22,23,[31][32][33][34][35]. Most of these were SYBR green-based systems; only three were probe-based.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these were SYBR green-based systems; only three were probe-based. Of the three probe-based qPCR, one was for identifying Australian mammals in Culex mosquito bloodmeals and did not include humans, pigs or dogs [23], another was for identifying bloodmeal hosts of biting midges and included humans and pigs but not dogs [33], and another was for identifying flea bloodmeals and included humans and dogs but not pigs [35]. Notably, the human probe in the latter flea bloodmeal study was tested here and found to cross-react with dog DNA.…”
Section: Discussionmentioning
confidence: 99%